1995
DOI: 10.1074/jbc.270.10.5642
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and Sequencing of an Intronless Mouse S-Adenosylmethionine Decarboxylase Gene Coding for a Functional Enzyme Strongly Expressed in the Liver

Abstract: A genomic clone for a mouse S-adenosylmethionine decarboxylase (AdoMetDC) gene was isolated from a cosmid library. Surprisingly, the gene proved to be intronless. With the exception of three base substitutions (changing 2 amino acids in the deduced protein), the 1002-nucleotide sequence of the open reading frame was identical to that of mouse AdoMetDC cDNA. Moreover, the gene contained a poly(dA) tract at the 3' end and was flanked by 13-base pair direct repeats. Our findings suggest that this gene has arisen … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
21
0

Year Published

1995
1995
2012
2012

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 67 publications
4
21
0
Order By: Relevance
“…It has been reported that the mouse genome contains another intronless Amd2 gene (Persson et al 1995(Persson et al , 1999. However, we have previously reported that the relative contribution of the enzyme encoded by Amd2 to total AdoMetDC activity is small, if any (Nishimura et al 1998).…”
Section: Although Various Tissues Of Heterozygous Amd1mentioning
confidence: 92%
“…It has been reported that the mouse genome contains another intronless Amd2 gene (Persson et al 1995(Persson et al , 1999. However, we have previously reported that the relative contribution of the enzyme encoded by Amd2 to total AdoMetDC activity is small, if any (Nishimura et al 1998).…”
Section: Although Various Tissues Of Heterozygous Amd1mentioning
confidence: 92%
“…Thus, differences between polyamine-starved and polyamine-replete cells in the incorporation of radioactive methionine into ODC diminished progressively with a decrease in pulse-label time, reaching a minimum with a pulse time of 4 min. In similar types of studies, Persson and co-workers did not find that the difference was abolished [156] [58]. Since newly synthesized ODC is a monomer that should bind with antizyme much more easily than preformed ODC, which is mostly a dimer, it is reasonable to suggest that newly synthesized ODC turns over much more rapidly than preformed ODC.…”
Section: Unsolved Problemsmentioning
confidence: 91%
“…However, this observation could not be generalized as examples of X-linked retrotransposons originating from autosomal precursors were also observed (32). Finally, situations have been reported in which functional processed genes and their originating intron-containing genes demonstrate a similar broad range of expression (the mouse S-adenosylmethionine decarboxylase gene (Amd2) (33) and the human eukaryotic initiation factor 4E2 gene (34)). Thus, it is difficult to support general rules correlating expression patterns of originating genes and retrotransposed gene copies.…”
Section: Discussionmentioning
confidence: 99%